Reputation Risk Management in Islamic Higher Education - Jufra, Arlita Aristianingsih; Akmal; Sulaeman, Nasrullah (Li Falah: Journal of Islamic Economics and Business, 2025)
This research aims to analyze the role of Islamic Religious Higher Education (PTKI) governance in Southeast Sulawesi, particularly in Kendari, through the lens of reputation risk management. Employing a qualitative approach with semi-structured interviews and thematic analysis, this study investigates institutional understanding of reputation risk and its governance mechanisms. The findings reveal a significant gap: while institutional leaders prioritize "normative legitimacy" through accreditation, there is a profound absence of formal risk management frameworks and dedicated units. Furthermore, the study identifies a disconnect between media influence and institutional response, where traditional assessment models overlook the volatility of social perception. Practical Implications: The study underscores the urgent necessity for PTKI to formalize risk governance by establishing dedicated Risk Management Units and integrating reputation risk into their long-term strategic planning. Institutions should shift from reactive crisis management to proactive mitigation by developing comprehensive risk maps and enhancing stakeholder literacy regarding institutional regulations. These steps are critical to ensuring institutional resilience and maintaining competitive advantage in an increasingly digitalized and scrutinized higher education landscape.